Factors Influencing Purchasing Intention Toward Electric Vehicle in Vietnam - Pham Van Tuan; Nguyen Thi Phuong Thao; Le Thi Thuy Linh; Tran Thi Le; Nguyen Thuy Linh; Hoang Minh Tuan (Journal of Social Commerce, 2022)
With the growth of the global electric vehicle industry, Viet Nam is proud to be one of the countries with an electric vehicle manufacturing company. This study will focus on government support, environmental perception, pricing perception, infrastructure attributes, and performance factors impacting the purchase intention of electric cars based on the theory of planned behavior (TPB) with variables mediators are attitude and subjective norms. A nationwide questionnaire survey of all ages with 406 valid samples was conducted from December 2021 to January 2022. The result showed that government support, environmental perception, pricing perception, infrastructure attributes, and performance factors positively influence both attitude and subjective norms, according to the SEM results, and attitude and subjective norms have a positive impact on Vietnamese people's intention to buy electric cars. The report has since provided guidance to the government and businesses on stimulating the growth of the electric car sector.